1982
DOI: 10.1128/mcb.2.9.1033
|View full text |Cite
|
Sign up to set email alerts
|

Mutations affecting the structure and function of immunoglobulin M.

Abstract: Using a hybridoma cell line which secretes hapten-specific immunoglobulin M (IgM), we have isolated a variety of mutants which produce abnormal immunoglobulin. Immunoglobulin was tested for the size and composition of the component heavy and light chains and for variable and constant region related functional and serological activities. Some mutants secrete IgM which seems to be defective in hapten binding; others make IgM which appears not to activate complement. Many of the mutants secrete monomeric as oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…IgM from the two strains had a similar profile after passage over the column, indicating that they have the same size and are assembled in a similar way (Fig. S1A), thus confirming previous observations (43,45). Moreover, IgM from both Cμ13 and BALB/c mice had an HA titer of 1:128 compared at the same IgM concentrations (∼0.87 mg/mL as measured by absorbance at 280 nm).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…IgM from the two strains had a similar profile after passage over the column, indicating that they have the same size and are assembled in a similar way (Fig. S1A), thus confirming previous observations (43,45). Moreover, IgM from both Cμ13 and BALB/c mice had an HA titer of 1:128 compared at the same IgM concentrations (∼0.87 mg/mL as measured by absorbance at 280 nm).…”
Section: Resultssupporting
confidence: 77%
“…Analysis of IgM with the same point mutation as the one introduced into the genome of the Cμ13 mice showed that the light chain and the μ-chain in mutant and WT IgM had the same size (45) and that >90% of both types of IgM was assembled in the form of pentamers (43). We show here that IgM in sera of Cμ13 and WT mice has the same size, the same ability to agglutinate SRBCs, and a similar half-life.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to many Ig secretion mutants previously described that have sizable deletions in their Ig genes (32,37) or synthesize only H or L chains (27). Though immunoglobulin binding protein, BiP, has been shown to be involved in proper assembly of Ig, we feel it unlikely that faulty interactions with BiP are responsible for Russell body formation .…”
Section: Mott Cell Hybridomas Often Secrete Igsmentioning
confidence: 61%
“…After the cells were incubated at 37ЊC for 2 days, supplemented medium was added to give a final concentration of 10 g of mycophenolic acid per ml, 15 g of hypoxanthine per ml, and 25 g of xanthine per ml (MHX medium) (28), and cells were plated at 5 ϫ 10 4 cells/ml. After 2 weeks the culture supernatants were tested for C determinants by enzyme-linked immunosorbent assay (ELISA) specific for the C 1 domain (38).…”
Section: Construction Of Targeting Vectorsmentioning
confidence: 99%